PEMBERDAYAAN WIRAUSAHA DALAM PENDEKATAN ADMINISTRASI PADA PERJANJIAN KERJA SAMA USAHA - Saniazahroh, Saniazahroh; Hidayat, Koerniawan (Jurnal Abdimas Bina Bangsa, 2024)
The cooperation agreement is an important aspect for business actors in entrepreneurship, especially in the people of the South Rawabadak area, North Jakarta. This activity was carried out with the aim of increasing the community's experience and understanding of business cooperation agreements. The implementation method in this activity is a direct socialization method in delivering material to the participants in this activity. By using this method, it attracts participants to actively participate which can be an evaluation and benchmark for the success of this socialization activity. It is hoped that this socialization activity can have a positive impact on the attention of the community, especially business actors to pay attention to the importance of business cooperation agreements, as well as encourage business actors to take an administrative approach in agreements that are also in accordance with the procedures in each business agreement